A longitudinal study of poor performance and subclinical respiratory viral activity in Standardbred trotters. Issue 1 (17th June 2015) - Back, Helena; Penell, Johanna; Pringle, John; Isaksson, Mats; Ronéus, Nils; Treiberg Berndtsson, Louise; Ståhl, Karl
Abstract : Introduction: While clinical respiratory disease is considered a main cause of poor performance in horses, the role of subclinical respiratory virus infections is less clear and needs further investigation. Aims and objectives: In this descriptive longitudinal study the relationship of markers of subclinical respiratory viral activity to occurrence of poor performance in racing Standardbred trotters was investigated. Material and methods: 66 elite Standardbred trotters were followed for 13 months by nasal swabs analysed with qPCR for equine influenza virus, equine arteritis virus, equine rhinitis B virus (ERBV), equine herpesvirus type 1(EHV‐1) and equine herpesvirus type 4 (EHV‐4) and serology to equine rhinitis A virus (ERAV), ERBV, EHV‐1 and EHV‐4, as well as the acute phase protein serum amyloid A (SAA). Findings on lab analyses were subsequently assessed for possible correlations to workload performance and trainer opinion measures of poor performance. Results: Despite occurrence of poor performance and subclinical viral activity the authors were unable to detect association neither between subclinical viral activity and poor performance, nor between SAA elevations and either viral activity or poor performance. Conclusions: Consistent with earlier study results, antibody titres to ERBV remained high for at least a year and few horses two years or older were seronegative to either ERAV or ERBV. In absence of clinical signs, serology to common respiratory viruses appears to have little diagnostic benefit in evaluation of poor performance in young athletic horses.